Idiomatic Expression Used in Jason Mraz’s Song in the Album Know and Its Possibility to be Used in ELT - Baharuddin Baharuddin (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2022)
This study aims to find the types of idiomatic expression and elaborate the meaning of idiomatic expression used in Jason Mraz’s song in the album ‘Know’ and its possibility to be used in ELT. Each song generally has idiomatic expression delivered to the listeners. This study focused to analyze phrases of idiom in Jason Mraz’s song lyrics. This study used theory of Makkai about Idiom Structure in English and applied descriptive qualitative method which concern in understanding the result of the data found. The data acquired from 10 songs in the album ‘Know’ in 2018. After analyzing, this study found 39 of idiomatic expressions, but only found 3 types of idiomatic expressions in the album such as Phrasal Verb Idiom, Tournure Idiom, and Irreversible Binomial Idiom from 6 types of idiom. Nine phrasal verb idiom, twenty three tournure idiom, and seven irreversible binomial idiom. Tournure Idiom is the majority used in the song lyrics of Jason Mraz ‘Know’. The researcher found the meaning of song lyrics generally describe about love. The existence of idiomatic expression is used to beautify and to clarify the contextual meaning of the song lyrics. Keywords: idiomatic expression; songs; lyric; english language teaching.